2010
DOI: 10.4049/jimmunol.1000667
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG1 Monoclonal Antibody against Human Collagen 17 Noncollagenous 16A Domain Induces Blisters via Complement Activation in Experimental Bullous Pemphigoid Model

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 58 publications
1
52
1
1
Order By: Relevance
“…Our previous study showed that the administration of Fab fragments to hNC16A into neonatal COL17-humanized mice inhibits the complement pathway and ameliorates skin detachment (10). We also reported that hIgG1 against hNC16A with mutations at the C1q-binding Fc portion has lower pathogenicity in neonatal COL17-humanized mice than has nonmutated hIgG1 (11). More recently, we demonstrated that passive transfer of F(ab9) 2 fragments of BP-IgG or rabbit IgG against hNC16A induces skin detachment in neonatal COL17-humanized mice (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous study showed that the administration of Fab fragments to hNC16A into neonatal COL17-humanized mice inhibits the complement pathway and ameliorates skin detachment (10). We also reported that hIgG1 against hNC16A with mutations at the C1q-binding Fc portion has lower pathogenicity in neonatal COL17-humanized mice than has nonmutated hIgG1 (11). More recently, we demonstrated that passive transfer of F(ab9) 2 fragments of BP-IgG or rabbit IgG against hNC16A induces skin detachment in neonatal COL17-humanized mice (13).…”
Section: Discussionmentioning
confidence: 99%
“…The HEK293 human COL17 cells used in this study were previously established (11). Briefly, the constructed plasmid pcDNA5/FRT (Invitrogen) that had been inserted with human COL17A1 cDNA (a gift from Dr. K.B.…”
Section: Establishment Of Hek293 Human Col17 Cells and Human Col17dncmentioning
confidence: 99%
See 2 more Smart Citations
“…Most recently, treatment with Fab mAb fragments in a passive-transfer model using COL17-humanized mice has proved that inhibition of the complement pathway can ameliorate skin detachment (41). Moreover, IgG1 mAb with mutations at C1q binding sites, reacting against NC16A, had less potential for blister formation (42). Previous experiments suggested that complement activation has primary importance in the pathogenesis of BP.…”
Section: Discussionmentioning
confidence: 99%